Performance of steers sired by bulls of different sizes. A comparison of Hereford steers sired by small, medium, and large size bulls. - Weber, A.D.; Mackintosh, D.L.; Good, D.L.; Smith, E.F. (Kansas Agricultural Experiment Station, 2012)
The Kansas, Oklahoma, and Ohio Agricultural Experiment Stations co-operated in this study, which was supported by grants from the American Hereford Association. The project involved comparisons of steer calves sired by small, medium, and large size bulls. Each sire group at each station was handled under the following systems of feeding and management: System I-immediate full feeding for 225 days. System II-a deferred full-feeding program in which the steer calves are wintered well, grazing without grain from May 1 to August 1, and then full-fed in dry lot 100 days. System III-the production of two-year-old grass-fat steers without the feeding of grain. Phases under this system include: wintering as calves without grain; grazing as yearlings a full season without supplemental feed; wintering as yearlings without grain; grazing as two-year-olds without supplemental feed and selling as slaughter cattle directly off pasture.
Keywords: Beef; Performance; Bulls; Size